Industrial Engineering Study Program, Faculty of Engineering, Nusantara PGRI University of Kediri, Indonesia - Hermin Istiasih; Elis Irmayanti; Bayu Surindra (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
This study aims to explain the intention to use OFD services within the TPB framework to improve consumer experience in using OFD and consumers' desire to order food during the COVID-19 pandemic and post-pandemic 19. In this study the variables observed were OFD, consumer desire, consumer experience, and the SDG framework (attitudes, subjective norms and behavioral controls). Every food choice is innovating products or services to address the challenges posed by the COVID-19 pandemic by enhancing the value of the consumer experience and stimulating consumer desire. Structural equation modeling (SEM) was used to verify the research hypothesis and to analyze the intention to use OFD services. An online survey was also conducted and a total of 300 questionnaires were distributed, invalid questionnaires were ignored with incomplete answers, and a total of 236 questionnaires were considered valid. The results of the study are as follows: (1) attitudes, subjective norms, and control of consumer behavior have a significant positive effect on the value of consumer experience in using OFD services before and consumer desires; (2) the value of consumer experience on the previous use of OFD services and consumer desires have a significant and positive effect on the effect of intention to use OFD services; and (3) the values of consumer experiences on the use of OFD services before and consumer desires have a mediating effect on attitudes, subjective norms, behavioral control, and intention to use OFD services. Based on the results of the analysis, OFD managers can identify the main factors that drive consumer intentions to use their services to formulate effective management strategies and create greater business opportunities for their organizations.